Mini-Open Technique for Gluteus Medius Tendon Repairs Is Associated With Low Complication Rates and Sustained Improvement in Patient Reported Outcomes at 2-Year Follow-Up - Matthew Quinn, M.D; Alex Albright, M.D; Victoria Kent, B.S; Patrick Morrissey, M.D; Luca Katz, B.S; Michael Kutschke, M.D; Nicholas Lemme, M.D; Ramin R. Tabaddor, M.D (Elsevier, 2024)
Purpose: To evaluate the efficacy of the senior author's hybrid "mini-open" technique for abductor tendon repair at 2-year follow-up. Methods: After institutional review board approval, we performed a retrospective review of prospectively collected data for all patients undergoing isolated mini-open gluteus medius tendon repairs from January 2018 to January 2022. Inclusion criteria included ongoing abductor pain refractory to nonoperative management, magnetic resonance imaging demonstrating gluteus medius/minimus tear, completion of preoperative patient-reported outcome measures (PROMs) including Modified Harris Hip Score (mHHS), Hip Outcome Score for Activities of Daily Living (HOS-ADL), Hip Outcome Score for Sports-Related Activities (HOS-SS), and visual analog scale (VAS) for pain and minimum 2-year follow-up. PROMs were assessed at preoperative, 6-month, 1-year, and 2-year postoperative intervals. Paired-sample t tests were used to compare the change in each outcome measure. The minimal clinically important difference (MCID) was calculated, and complications were recorded. Results: Sixty-one patients (59 female, 96.7%) with an average age of 61.4 ± 1.3 years were included. The mean follow-up was 25.9 ± 1.13 months. mHHS improved from a mean of 47.2 preoperatively to 68.9 at 2 years (P < 0.001), HOS-ADL from 54 to 78.9 (P < 0.001), HOS-SS from 37 to 66.5 (P = 0.015), and VAS from 13.3 to 7.4 (P = 0.001). The MCIDs for mHHS, HOS-ADL, HOS-SS, and VAS were 11.1 (60% achievement), 6.1 (78.6% achievement), 9.7 (80.3% achievement), and 14.5 (75.4% achievement), respectively. Two patients experienced retears (3.2%), with no other complications reported. Conclusions: The mini-open technique for abductor tendon repair provides sustained improvement in both pain and function-related PROMs at 2-year follow-up with comparable complication rates to endoscopic and open techniques in 1 surgeon's practice. Level of Evidence: Level IV, therapeutic retrospective case series.